2009
DOI: 10.1038/jhh.2009.44
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional survey of relationship between serum TSH level and blood pressure

Abstract: It is still controversial whether subclinical hypothyroidism and euthyroidism affect blood pressure. The study aimed to explore the relationship between different levels of thyroid-stimulating hormone (TSH) and blood pressure in the participants with subclinical hypothyroidism and euthyroidism. A total of 1319 participants were administered a questionnaire survey, and their blood pressure, height and body weight measurements were taken. Blood samples were taken to test serum TSH. FT3 and FT4 were further exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
88
4
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(97 citation statements)
references
References 16 publications
3
88
4
2
Order By: Relevance
“…This result is in accordance with the hypothesis that SCH leads to atherosclerosis by augmenting classical CV risk factors such as dyslipidaemia and systemic hypertension (6). Indeed, positive correlations between serum TSH and blood pressure (35,36) and between TSH and serum lipids (2, 37, 38) have been demonstrated in several studies. In addition, a potential relationship between SCH and metabolic syndrome and a reduction in insulin sensitivity have also been proposed (39,40), and SCH also seems to be associated with additional CV risk factors.…”
Section: Discussionsupporting
confidence: 75%
“…This result is in accordance with the hypothesis that SCH leads to atherosclerosis by augmenting classical CV risk factors such as dyslipidaemia and systemic hypertension (6). Indeed, positive correlations between serum TSH and blood pressure (35,36) and between TSH and serum lipids (2, 37, 38) have been demonstrated in several studies. In addition, a potential relationship between SCH and metabolic syndrome and a reduction in insulin sensitivity have also been proposed (39,40), and SCH also seems to be associated with additional CV risk factors.…”
Section: Discussionsupporting
confidence: 75%
“…In studies comparing euthyroid subjects with subclinical hypothyroid subjects, people in the subclinical hypothyroid group have a higher prevalence of high blood pressure and dyslipidemia (1,2). Also in the euthyroid range, serum TSH is positively associated with blood pressure, total cholesterol (TC), triglycerides, and LDL, and negatively associated with HDL (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…4 Within the past 5 years, six large cross-sectional studies on this topic have produced conflicting results. [5][6][7][8][9][10] Three studies concluded that subjects with subclinical hypothyroidism had a significantly higher systolic blood pressure (SBP) than euthyroid subjects (age, sex and body mass index adjusted). 5,9,10 However, discrepancies between study results may have arisen from differences in the level of adjustment for other cardiovascular risk factors among the included studies.…”
Section: Introductionmentioning
confidence: 99%